Effect of Adhesive Concentration on Briquette Characteristics from a Mixture of Cocoa Shells and Groundnut Shells as an Alternative Fuel - Huda, Ahmad Akromul; Tawaqqal, Akbar; Hidayatullah, Syarif; Wirasansir, Genta (Jurnal Agrotek Ummat, 2025)
Agricultural wastes such as cocoa shells and groundnut shells hold significant potential as environmentally friendly alternative energy sources, particularly in West Nusa Tenggara Province, where these commodities are produced in abundance. However, their utilization as biomass energy materials remains limited and underdeveloped. In response to this potential, this study aims to evaluate the effect of varying tapioca starch adhesive concentrations on the characteristics of briquettes made from a mixture of cocoa shell charcoal and peanut shells. The research was conducted experimentally using three adhesive concentrations (10%, 20%, and 30%), with tests performed on calorific value, moisture content, ash content, and flame duration. The results revealed that increasing the adhesive concentration tended to decrease the calorific value and increase both the moisture and ash contents, although it extended the flame duration. The briquettes with 10% adhesive concentration exhibited the best performance, achieving a calorific value of 5,310 cal/g, a moisture content of 7.57%, an ash content of 7.56%, and a flame duration of 73 minutes. These values comply with the Indonesian National Standard (SNI) for charcoal briquettes, which require a minimum calorific value of 5,000 cal/g, a maximum moisture content of 8%, and a maximum ash content of 8%. These findings highlight the importance of proper adhesive formulation to improve the quality of local biomass-based briquettes and support the transition toward clean and sustainable energy..